Pheromone blend and sexual attraction in Bt-susceptible and resistant fall armyworm (Spodoptera frugiperda). - Machuca Mesa, Laura Marcela (2019)
Location and attraction of sexual partner is a necessary condition for sexual reproduction in insects. Among moths, chemical signals called sex pheromones are used to ﬁnd a potential mate. Female moths produce pheromones active over long distances, which induce mate-location and mating. Biotic and abiotic factors inﬂuence production and emission of female sex pheromones, and male responsiveness. Age, pathogens, con- speciﬁc pheromones, mating status, temperature, day length, light inten- sity, relative humidity, wind speed, atmospheric conditions, geographic variations, host plants, and insecticide resistance affect sexual communication. In this thesis, we focused on the changes in sex communication of Spodoptera frugiperda (Lepidoptera: Noctuidae) caused by the resistance to maize hybrids expressing Bt toxins (Cry1Fa). First, we evaluated the sex pheromone production of resistant and susceptible (homozygous and heterozygous) individuals. We observed differences among the genotypes in the amount of major component (Z9-14: Ac) and the relative proportion of the minor component during calling days and hours of scotophase. The main changes were observed in the titer of crucial minor component (Z7-12: Ac). The variations in the minor sex pheromone component can generate differences in sexual partner attraction. Second, we evaluated the male response to the calling female in the laboratory and the ﬁeld. We showed that susceptible males respond less to resistant females both in the laboratory and ﬁeld. Our results showed that Bt-resistance modify the sexual communication variables including pheromone production and male response. Both the pheromone variations and differences in male responsiveness can generate assortative mating among the insect genotypes. Assortative mating between resistant females and resistant males increasexii the resistance allele in the population favoring ﬁeld resistance development to the Bt crops. Finally, the assortative mating negatively affects the high dose/refuge strategy proposed to delay the resistance in the ﬁeld.